Rural contradictions and class consiousness: Migrant labour in historical perspective : the Ciskei in the 1880s and 90s - Lewis, Jack (My University, 1985)
In a recent work Shula Marks and Richard Rathbone have brought together a collection of articles intended to expand understanding "both of the overall contours of the political economy and more especially of the black experience." The theoretical discourse in which it is intended that this ‘experience’ should be analysed is explicitly that derived from Edward Thompson, both in his work on the ‘making’ of the English working class and subsequently in his attack on the methodologies of ‘structuralism’ Marks and Rathbones’ main concern is with the active ‘agency’ exerted by Africans in the process of proletarianisation. The central concept which they adopt is that of ‘consciousness’, which they define, after Thompson, as "the way in which...experiences are handle, in cultural terms: embodied in traditions, value systems, ideas and institutional forms".
African Studies Seminar series. Paper presented May 1985
Keywords: Migrant labor. South Africa. Ciskei; South Africa. Economic conditions